Ways of Value-Based Educational Management in the Light of Islamic Education: An Analytical Study - Soud , Hosni (Dirasat: Educational Sciences, 2021)
The study aims to clarify the ways of educational management for the value of leadership in the light of Islamic education, which was represented by the personality of the Messenger of Allah- may Allah’s prayers and peace be upon him. The study followed the descriptive analytical approach. The study showed that leadership was represented in the attributes of the Prophet – may Allah’s prayers and peace be upon him - and some of them were related to the personality of the Prophet – may Allah’s prayers and peace be upon him, and others were related to the general public.The study also showed that leadership criteria are associated to the Islamic guides which had its impact on leaders personalities and values by benefiting indiviuals and societies. The study sheds light on the importance of applying the educational management concept to the leadership value in Islam and the most important criteria and values that distinguish them.